Spatial and seasonal determinants of arthropod community composition across an agro-ecosystem landscape - P. Burgess; G.S. Betini; A. Cholewka; J.R. deWaard; S. deWaard; C. Griswold; P.D.N. Hebert; A. MacDougall; K.S. McCann; J. McGroarty; E. Miller; K. Perez; et al. (FACETS)
We used Malaise traps to sample arthropod community composition at biweekly intervals across an agroecosystem landscape in southern Ontario, Canada, to evaluate the relative impact of site spacing, seasonal timing, weather conditions, local plant community attributes, and agricultural extent across the local landscape on spatial and temporal variation in arthropod community composition. The 15 field sites sampled spanned a wide gradient of agricultural extent that in isolation had a strong impact on spatial variation in arthropod community composition. DNA metabarcoding of the samples identified >10 000 different arthropod biodiversity index numbers. Local variation in plant community composition and canopy cover best explained variation in arthropod community dissimilarity. Weather variables followed closely in explanatory power, driven primarily by seasonal variation in temperature. Significant effects of time remained after accounting for environmental variables, with little independent effect of spatial distance. The proportion of agricultural land at the landscape scale had little detectable effect after controlling for the influence of the other environmental variables. Our results suggest that plant community composition, cover, weather conditions, and seasonality structured the arthropod community to considerable degree.